English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

y= -x^2+x+2 I need to have this in y terms, so x= ?

2007-05-31 10:59:13 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

y= -(x-.5)^2+2.25
so y-2.25=-(x-.5)^2
so (2.25-y)=(x-.5)^2
and finally, x=+-sqrt(2.25-y) +.5

2007-05-31 11:06:16 · answer #1 · answered by bruinfan 7 · 0 0

Multiply by -1 on both sides
-y = x^2 - x - 2
x^2 - x = 2 - y
Complete the square
x^2 - x + (1/2)^2 - (1/2)^2 = 2 - y
(x - 1/2)^2 - 1/4 = 2 - y
(x - 1/2)^2 = (9/4) - y
x - 1/2 = +/- sqrt ( (9/4) - y)
x = (1/2) +/- sqrt ( (9 - 4y) / 4 )
Answer:
x = (1/2) +/- (1/2) sqrt ( 9 - 4y)

You could also use the quadratic formula instead of completing the square.

2007-05-31 18:14:47 · answer #2 · answered by chavodel93550 3 · 0 0

y = -x² + x + 2
-y = x² - x - 2
2-y = x² - x
2 - y + 1/4 = x² - x + 1/4
5/4 - y = (x - 1/2)²
±√(5/4 - y) = x - 1/2
1/2 ± √(5/4 - y) = x

2007-05-31 18:08:27 · answer #3 · answered by Philo 7 · 0 0

-y= x^2-x-2 (I got rid of the negative on the x^2)
-y+2=x^2-x (complete the square)
-y+2+1/4=x^2-x+(1/4)
-y+9/4=(x-1/2)^2
+/-sqrt(-y+9/4)=x-1/2
x= +/- sqrt(-y+9/4)+1/2

2007-05-31 18:07:41 · answer #4 · answered by hawkeye3772 4 · 0 0

That will not be a function.

2007-05-31 18:08:47 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers